2009
DOI: 10.1159/000245160
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Consecutive Study of Post-Tonsillectomy Haemorrhage

Abstract: Objective: To analyse consecutive material over a period of 4 years concerning the incidence and consequences of post-tonsillectomy haemorrhages (PTH). Design: Prospective study. Setting: University hospital. Participants: All non-oncological cases of tonsillectomy (TE) and adenotonsillectomy (TA) performed at the ENT department at the Karolinska University Hospital between March 2000 and April 2004. Main Outcome Measures: Rate, timing and classification of PTH. Results: During the study period, 2,813 cases (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 15 publications
6
33
0
10
Order By: Relevance
“…This is similar to what Attner et al [15] reported, where they noted higher secondary post-tonsillectomy bleed in a review of 2,813 cases over 4 years (1.9 vs. 5.5%). These new data could be a basis of change in existing routine post-operative care.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to what Attner et al [15] reported, where they noted higher secondary post-tonsillectomy bleed in a review of 2,813 cases over 4 years (1.9 vs. 5.5%). These new data could be a basis of change in existing routine post-operative care.…”
Section: Discussionsupporting
confidence: 90%
“…As such, we were only able to obtain information about the incidence of serious complications associated with tonsillectomy in one half of the selected articles. Further limitations of this review are that (1) there is currently no agreed-upon definition of what constitutes a ‘serious' complication following tonsillectomy, although this term is used sometimes [11], (2) minor bleeding episodes can later become more serious life-threatening events [6,11,12,13,14,15], and (3) it is commonly accepted to distinguish primary bleeding (<24 h) from secondary bleeding (>24 h). Attempts were made repeatedly to classify PTH in the past [16,17,18,19,20,21], but studies rarely report the severity or amount of blood loss during a hemorrhagic event.…”
Section: Discussionmentioning
confidence: 99%
“…Seconder tonsil haemorrhages tend to occur in the first week after surgery (5,28) and rarely require surgery after the first 10 days (29,30). When the patient data in the study were examined, it was observed that the hemorrhage occurred mainly between postoperative 6th and 10th days and there was no hemorrhage requiring surgery after the 13th day of surgery.…”
Section: Discussionmentioning
confidence: 99%